The Utilization of School Land for Chili Planting as a Strategy to Support School Operational Financing at SMA Negeri 4 Kupang - Ero, Priska Tri; Minding, Enjelita; Taebenu, Melania Desry; Sonbai, Hermy Irianti; Ee Tea, Maria Giuseppina; Hada, Thomas Herculanus Ola; Bone, Matilda Pia (The Future of Education Journal, 2026)
The Merdeka Belajar Kampus Merdeka (MBKM Mandiri) program is a mandatory activity for every student of the Faculty of Teacher Training and Education at Widya Mandira Catholic University, Kupang, to acquire new knowledge and gain practical experience from the field activities. The MBKM activities outside the classroom involve community service. The community service is carried out through land utilization for chili planting at SMA Negeri 4 Kupang, East Nusa Tenggara Province. This activity aims to promote the green school movement and foster an entrepreneurial spirit among students to support school operational financing. This community service uses a participatory method, where this method involves direct collaboration between the KKN participants and the school community. The results of this study show that the social service activity provides significant benefits to the school, as it can be used as a contextual learning tool based on project-based learning. Additionally, students not only gain knowledge about the farming process but also have the opportunity to develop it into a school entrepreneurship activity that can support the school’s operational financing.